Progress of thematic repositories and megajournals: Perspectives in 2018 - López-Borrull, Alexandre (Anuario ThinkEPI, 2018)
The evolution of several thematic repositories that appeared in 2017 is described, as well as some of the future trends related to the issue. Also, the future of megajournals is discussed, with emphasis on its viability, business model, and consolidation strategies.
Keywords: Disciplinary repositories; Megajournals; ArXiv; ChemRxiv; Open Science Framework; PLoS one.